Studies in law, politics and society. Vol. 31 - Sarat, Austin; Ewick, Patricia (JAI, 2003)
This volume presents articles by an interdisciplinary and international group of scholars spanning the social sciences, humanities, and law. It examines new perspectives on political relationships, politics and legal reform, and law and the family.